Some aspects of the legal regulation of higher education in the countries of the European Union as a positive experience in the process of internationalization and development of international universities in Kazakhstan - Berdybaev Н.М. (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2023)
The article examines the fundamentals of the legislation of some countries of the European Union (EU) in the field of higher and postgraduate education, examines the legal policy and experience of these countries in implementing regulatory legal acts, as a result of which it is concluded that, in general, the legislation of individual EU countries is homogeneous and aimed at internationalization, intercultural cooperation and improvement the quality of higher education. At the same time, the motives for the internationalization processes leading to the emergence of international universities and their implementation vary depending on the type of university and the national system in which it operates, since European countries are heterogeneous in their economic, territorial, cultural and other aspects. For this reason, it seems necessary to study the legislation of EU countries, taking into account the classification of States by territorial and economic scale, taking into account the later accession of some Eastern European countries to the EU. The article shows the direct and indirect influence of the experience of advanced EU countries in the field of higher education on the emergence and development of international universities with the participation of the Republic of Kazakhstan. The positive experience and legislative framework of the EU countries accelerated the processes of internationalization, transition to a three-level model, strengthened the trends of international cooperation in ensuring the quality of education, intercultural exchange and mobility of students and teachers of international universities.